Notes on Oxypetalum R. Br. (Apocynaceae, Asclepiadoideae) in Bolivia and Peru / D. J. Goyder & J. F. Pereira - Goyder, David J.; Pereira, Jorge Fontella (2007)
Two new species of Oxypetalum R. Br., O. fuscum and O. flavopurpureum, from Bolivia and Peru are described and illustrated, Gothofreda pearsonii Rusby is transferred to Oxypetalum, and O. apoloense (Rusby) Dorr is placed in synonymy under O. balansae Malme. The latter name is lectotypified.
il. byn
Keywords: Asclepiadaceae; Oxypetalum; Flora; Bolivia; Peru